Marine Natural Products as Anticancer Agents 2.0 - Alves, Celso; Diederich, Marc (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Global cancer incidence and death are expected to increase in the next decades. Inappropriate therapeutic regimens and tumor recurrence due to the development of drug resistance are two major clinical challenges impacting poor patient outcomes, which is critical to the discovery and development of new anticancer drugs. Over the last few decades, the marine environment has proved to be a key source of molecules with potent anticancer properties. The Special Issue, "Marine Natural Products as Anticancer Agents 2.0", gathered eleven publications, including two reviews and nine research articles, about the anticancer activities of marine natural and/or derived products on in vitro 2D and 3D cellular models, and/or in vivo models of colorectal, breast, lung, myeloma, liver, leukemia, and melanoma cancers. Altogether, the eleven scientific papers published in this Special Issue provide an exciting overview of marine natural products as potential anticancer agents.